Antibiotic profiling of bacterial isolates obtained from turkey and chicken in selected farms in Ibadan, Nigeria (2019)
In recent times, the prevalence of antimicrobial drug resistance has increased tremendously due to a number of factors including use of human drugs for the treatment of animal diseases, leading to the transfer of antibiotic resistance in terms of antibiotic residues in poultry meat to pathogenic bacteria. This study determined the antibiotic profiles of bacterial isolates in poultry cloacal swabs from selected farms in Ibadan. Fifty and twenty cloacal swabs were collected aseptically from turkey and chicken at Apete and University of Ibadan research farm respectively. The samples were immediately transported to the laboratory for microbiological analysis. Thus, the cloacal swabs were screened using MacConkey agar, blood agar and xylose lysine deoxycholate agar. Isolates were identified using standard microbiological techniques and tested to ten different antibiotic discs according to Kirby-Bauer procedure. Sixty-one and thirteen different isolates were detected from turkey and chicken cloacal swabs respectively. Of the turkey isolates, Pseudomonas had the highest occurrence of 25% while Escherichia coli (46%) had the highest occurrence of the chicken isolates. The Gram-negative isolates showed high resistance to augmentin (69%), streptomycin (69%), sulphamethoxazole (78%) and chloramphenicol (82%). Staphylococcus species which was the only Grampositive isolate in this study was greatly resistant to gentamicin (83%). Both the turkey and chicken isolates had different antibiotic resistance rates and patterns with a huge percentage (86%) of them being multi-drug resistant. This work observed a higher resistance to many of the commonly used antibiotics in the poultry industry thereby, posing a public health risk since most of these drugs are used for treatment of human infections